Dynamics of acid phosphatase production by cell suspension system and its further characterization - Khan, Saima; Mallubhotla, Sharada; Manzoor, Malik Muzafar; Pagoch, Sandeep Singh; Ahuja, Ashok (Emirates Journal of Food and Agriculture, 2023)
The current study compares the influence of media engineered media on production of acid phophatase (APase) with its characterization in suspension cell cultures of Atropa acuminata, authenticated by rbcL and ITS. Various parameters like pH, inoculum size, temperature, nutrient sources in the medium were optimized for APase hyperproduction in in vitro conditions. APase production was accomplished to be evidently amplified at 5% inoculum size (94.90 U/gFW), pH 5.0(99.75 U/gFW) and incubation temperature of 30°C (91.5U/gFW). Sucrose as carbon and ammonium nitrate as nitrogen sources were eminently suited for maximum enzyme harvest (91.20 U/gFW and 94.56 U/gFW). The APase activity was observed to be distinctly increased in phosphate (Pi) starved suspension cells (197.84 U/gFW). Overall, 6.5 fold increase in APase activity was achieved as compared to the activity before optimization studies. Hence the present Apase production and its activity from Atropa acuminata suspension culture may have apparent use for future industrial, agricultural and biotechnological application. Keywords: Acuminata; Acid phosphatase; p-nitrophenylphosphate; Suspension cells; Pi-starvation